National Security Narratives and the Expansion of Executive Power: A Legal-Political Perspective on Emergency governance - Rengga Kusuma Putra (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2026)
The increasing complexity of contemporary security threats has led governments worldwide to adopt emergency governance mechanisms that expand executive authority in the name of national security. While such measures are often justified as necessary responses to terrorism, public health crises, cybersecurity threats, and geopolitical instability, they also raise concerns regarding constitutional limits, democratic accountability, and the preservation of the rule of law. This study examines how national security narratives function as instruments of political legitimation that facilitate the expansion of executive power during periods of emergency governance. The research employs a doctrinal legal research approach combined with political analysis to investigate the interaction between legal frameworks governing emergency powers and political processes that shape public acceptance of extraordinary governmental authority. The analysis draws upon constitutional provisions, emergency legislation, judicial decisions, policy documents, and scholarly literature concerning national security, executive authority, and democratic governance. The findings demonstrate that the expansion of executive power is not solely a legal consequence of emergency conditions but is significantly influenced by the political legitimation generated through security narratives. The study develops the  Security–Legitimation–Executive Expansion (SLEE)  framework, which explains how the construction of security threats produces political legitimacy that enables the concentration of executive authority and reshapes institutional power relations. The findings further reveal that the risks associated with emergency governance emerge primarily when extraordinary powers are exercised without effective legislative oversight, judicial review, transparency, and temporal limitations. The study contributes to the literature on emergency governance, constitutionalism, and national security by highlighting political legitimation as a critical mechanism linking security narratives to executive power expansion. It also provides policy implications for designing emergency governance systems capable of balancing effective security responses with democratic accountability and constitutional safeguards.